(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This is a reading of the first two novels of Adolfo Bioy Casares in the context of an interrogation about the status of the utopian literature and its crisis in the last century. In first place we take a quick look to the complex structure of fiction in utopian literature and the significance of this problem in the historical development of the genre. Then, we interpret the texts of Bioy as narrative response to the problem about the relationship among fiction and reality in the production of utopian discourse, assuming the transformation of reality in fiction by the mass-media contemporary culture.